Kościół na drodze ku „Nostra aetate”. Zarys historii relacji chrześcijańsko-żydowskich do czasów nowożytnych - Tulej, Andrzej (Warszawskie Studia Teologiczne, 2017)
This present study is a review of the most important statements of the Church contained in the conciliar decisions and papal documents on Jews and Judaism as well as on the relations between Jewish and Christian communities in the Middle Ages and in the Modern Era. The texts selected refer to both the religious and economic aspects, as well as the administrative aspect. Some statements have a negative overtone and have at times been described as anti-Semitic; however, more commonly, they express the Church's concern for the proper place and rights of the Jewish communities living in the neighbourhood of the Christian environment.